Peluang Penelitian UI/UX pada Pengembangan Aplikasi Mobile: Systematic Literature Review - Unggul Utan Sufandi; Denisha Trihapningsari; Widya Mellysa (LPPM Universitas Dian Nuswantoro, 2022)
Mobile application is one form of information technology development that continues to increase from year to year. In the development of the digital world, it is increasingly encouraging to increase the affordability of the use of mobile devices (smartphones) to generate the most sustainable technological growth. This enormous growth in its development has given impetus to smartphone manufacturers to produce new applications on mobile devices to meet user needs. A mobile application development must have user interface and user experience aspects as part of the human-computer interaction (HCI) discipline. Mobile applications under development can run on Android and iOS platforms. This study aims to identify research opportunities in the UI/UX aspect of mobile application development whose data was obtained from related journals in 2017-2021 to provide an overview of the latest studies on research related to UI/UX mobile applications and provide analysis on topics and areas that do not have enough information and what factors to focus on. This study uses the Systematic Literature Review (SLR) method. The result of this research is to provide a systematic literature review of existing studies on UI/UX mobile applications. This research is expected to be useful for the HCI community in seeing the UI/UX description in the development of mobile applications to shape the direction of future research.